1986
DOI: 10.1021/bi00369a030
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an associated equilibrium folding intermediate of bovine growth hormone

Abstract: In the preceding paper [Havel, H. A., Kauffman, E. W., Plaisted, S. M., & Brems, D. N. (1986) Biochemistry (preceding paper in this issue)], an associated intermediate was shown to be highly populated during the equilibrium denaturation of bovine growth hormone. In this paper, we describe its partial characterization and propose a mechanism for association. The associated equilibrium intermediate is populated under conditions that induce partial denaturation and at protein concentrations greater than 0.2 mg/mL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
53
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(60 citation statements)
references
References 16 publications
7
53
0
Order By: Relevance
“…Their three-dimensional structure is that of four-helix bundle with the helices arranged in an antiparallel fashion (1). Previous folding studies of bovine growth hormone (bGH) have demonstrated that under conditions of partial denaturation a stable intermediate is formed that is associated (2)(3)(4). The solubility ofthis species was investigated and was shown to be less soluble than the native or denatured conformations (5).…”
mentioning
confidence: 99%
“…Their three-dimensional structure is that of four-helix bundle with the helices arranged in an antiparallel fashion (1). Previous folding studies of bovine growth hormone (bGH) have demonstrated that under conditions of partial denaturation a stable intermediate is formed that is associated (2)(3)(4). The solubility ofthis species was investigated and was shown to be less soluble than the native or denatured conformations (5).…”
mentioning
confidence: 99%
“…Amphiphilic a-helices can be important structural elements in the folding pathway. For example, a helix composed of residues 110-127 in bovine growth hormone is thought to provide a distinct hydrophobic surface for a long-range intramolecular interaction early in the folding process (22,23 Proc. Natl.…”
Section: Resultsmentioning
confidence: 99%
“…At the junction between the productive folding and aggregation pathways, the folding reaction is in kinetic competition with the aggregation of the partially folded species. During folding, certain sites on the surface of the folding intermediates may cause the polypeptide chains to be susceptible to self-association (Zettlmeissl et al, 1979;Brems et al, 1986;Cleland & Wang, 1991).…”
mentioning
confidence: 99%